Syntheses and characterization of Schiff base ligands and their Ir(III) complexes as coating for phosphor-converted LEDs - Canisares, Felipe S.M. [UNESP]; Bispo-Jr, Airton G. [UNESP]; Pires, Ana M. [UNESP]; Lima, Sergio A.M. [UNESP] (Elsevier, 2020)
Ir(III) complexes find several applications in light conversion molecular devices (LCMD) such as in solid-state lighting (SSL). Although, a couple of blue or green-emitting Ir(III) complexes are found so far, there is a lack of near-UV-to-red downshifting converter Ir(III) complexes to be used as coatings of near-UV-excited white-light-emitting diodes (WLEDs). Thus, in this study, we introduce the syntheses of two ligands named as 2-(((3-methyl-1-phenyl-1H-pyrazol-5-yl)imino)methyl)phenol (BS1) and 5-(diethylamino)-2-(((3-methyl-1-phenyl-1H-pyrazol-5-yl)imino)methyl)phenol (BS2) and their use to synthesize two new red-emitting iridium complexes, Ag[Ir(ppz)2(BS1)] and Ag[Ir(ppz)2(BS2)]. BS1 and BS2 structures were deeply investigated theoretically and experimentally, and they display emission in the yellow and green spectral region under UV excitation, respectively. Ag[Ir(ppz)2(BS1)] and Ag[Ir(ppz)2(BS2)] features emission characterized by a broadband centered with color coordinates of (0.659;0.337) and (0.612;0.380), respectively, both in the red spectral region, with 100 % of color purity. To demonstrate their application in SSL, BS1 and Ag[Ir(ppz)2(BS1)] were used to coat commercial near-UV-emitting LEDs (395 nm). The radiant stability of the prototypes overseen for 24 h attests that the emission intensity of the Ag[Ir(ppz)2(BS1)]-LED prototype decreases only 10 %, confirming that the complex matches with the desired photostability and qualifying this complex to be used as coatings of near-UV excited white-light-emitting diodes.
Keywords: Downshifting converter; Iridium(III); Light conversion molecular devices (LCMD); Photoluminescence; Red emitter; Solid-state lighting (SSL); UV-LED; WLEDs